2021
DOI: 10.1136/bmjopen-2021-049650
|View full text |Cite
|
Sign up to set email alerts
|

ARCADIA study protocol: a phase II, randomised, double-blind, placebo-controlled clinical trial to assess the safety and efficacy of AZD1656 in patients with diabetes hospitalised with suspected or confirmed COVID-19

Abstract: IntroductionCOVID-19, caused by SARS-CoV-2, remains a global pandemic that has affected more than 100 million people worldwide with over 4.8 million deaths as of October 2021. Patients with diabetes have both an increased susceptibility to SARS-CoV-2 infection, enhanced disease severity and increased risk of mortality. The challenge presented in these patients is both to improve glycaemic control—which itself may confer a survival advantage—and to help maintain or restore immunological homeostasis. The specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Among the partial GKAs, AZD1656 and PF-04937319 are the two leading candidates evaluated in phase 2 trials. PF-04937319 is currently being studied in China in phase 3 trials 56 , and AZD1656 has shown encouraging outcomes for the reduction of overall coronavirus disease 2019 mortality in patients with diabetes in the ARCADIA study 50 . A liver-selective GKA, TTP399, which is chemically modified to optimize its uptake into hepatocytes and prevent its entry into pancreatic beta cells, has been developed for T2D and was shown to achieve sustained glycemic control without dyslipidemia with 6 months of treatment 33 .…”
Section: Any Hypoglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Among the partial GKAs, AZD1656 and PF-04937319 are the two leading candidates evaluated in phase 2 trials. PF-04937319 is currently being studied in China in phase 3 trials 56 , and AZD1656 has shown encouraging outcomes for the reduction of overall coronavirus disease 2019 mortality in patients with diabetes in the ARCADIA study 50 . A liver-selective GKA, TTP399, which is chemically modified to optimize its uptake into hepatocytes and prevent its entry into pancreatic beta cells, has been developed for T2D and was shown to achieve sustained glycemic control without dyslipidemia with 6 months of treatment 33 .…”
Section: Any Hypoglycemiamentioning
confidence: 99%
“…GKAs have also been developed for diseases other than T2D, including TTP399 for type 1 diabetes (T1D) 49 and AZD1656 for reducing mortality in patients with diabetes who were infected with severe acute respiratory syndrome coronavirus 2 (ref. 50 ).…”
mentioning
confidence: 99%
“…On days 0–3, 4–7, and 10–21 after diagnosis, participants who were alive were staged according to the 8-point WHO Clinical Progression Scale. 7 Electronic case report forms (MARVIN EDC; XClinical, Munich, Germany) were used for data compilation. For UPP, 10-mL urine samples were collected in borated test tubes (ExactoBac-U; Sarstedt, Nümbrecht, Germany) and kept at –20°C or less until assayed.…”
Section: Methodsmentioning
confidence: 99%